The Effect of Customer Service Performance and Sign Placement Facilities on Passenger Satisfaction Levels at Zainuddin Abdul Majid International Airport - Safira Fitri; Arif Fakhrudin (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
Customer Service is any activity that is intended or intended to provide customer satisfaction, through services that can fulfill the desires and needs of customers. Sign facilities are signs or information that are placed or installed at airport terminals, made clear, easy to understand and function to explain or provide instructions, warnings, regulations, prohibitions and orders for all users or service users at the airport. The purpose of this study is to find out how much influence the performance of Customer Service and Sign placement has on the level of passenger satisfaction at Zainuddin Abdul Majid International Airport. This study uses quantitative data. The data used in this study were taken from primary data based on questionnaires distributed to passengers at Zainuddin Abdul Majid International Airport from August to October 2022. With a total of 150 people, the data analysis technique used was Multiple Linear Regression Analysis, T Test , F Test and Coefficient of Determination. The results showed that H1 was rejected and H2 was accepted, which means that the calculation results of the F test showed the calculated F value = 0.829181 ftable value = 0.737812. It is very clear that H1 and H2 are accepted. The T test shows a significant value of the X1 variable to the Y variable, namely = 0.003244 Less than the threshold value Significance = 0.05 means that Customer Service Performance has a significant effect on Passenger satisfaction and a significant value of the Variable X2 to Variable Y, namely = 0.040887 Smaller than the threshold value. Significance = 0.05 means that the Placement of Sign Facilities has a significant effect on Passenger satisfaction. The results of the Coefficient of Determination test which shows how much the X1 variable is Customer Service performance and the X2 variable is the placement of Sign Facilities on the Y variable passenger satisfaction is known to be a determination coefficient of 78.7%, which means that the X1 variable is Customer Service performance and the X2 variable is the placement of Sign Facilities. Y variable is passenger satisfaction. contributed 78.7% to the Y variable of passenger satisfaction with a Correlation Value = 0.92087 (Very Strong).